D The Use Of Limited Land Through Hydroponics Technology for Ecogreen and Enhancing Entrepreneurship Motivastion to Improve the Family Economy Aisyiyah Cadres at PCM Jetis Yogyakarta - Desi Susilawati Susilawati; Putri Rachmawati Rachmawati; Rinasa Agistya Anugrah Anugrah; Ervina Ratna Ningsih Ningsih; Muhammad Nabil Natsir Natsir (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Technological developments in agriculture are increasing rapidly every year. One of the technologies that deserves to be disseminated is hydroponic technology [1]. This is because of the increasing scarcity of agricultural land as a result of the large number of industrial and service sectors, so conventional agricultural businesses are increasingly uncompetitive due to high land prices. Cultivation technology Agriculture with a hydroponic system is used as an alternative for people who have limited land or yard space so that it can be used as an adequate source of income. Entrepreneurship is one of the efforts of the pesantren to produce graduates who can have a personal independence. This community service program was carried out to meet support and encourage entrepreneurship that makes personal independence. The Community Service Program was carried out the hydroponic plant cultivation to support the independence Aisiyah Cadres Muhammadiyah Branch Jetis Yogyakarta This program was intended so that students can learn directly the Hydroponic cultivation system as a provision for self-development for students who have graduated. The dedication program consists of 2 sessions, the first is exposure and discussion with hydroponic materials, the second session consists of installing hydroponic installation, nursery training, planting seeds in the hydroponic system, wick system and nutrient film system.The Output of this program are the increased knowledge, understanding, and skills of Aisyiyah cadres related to the implementation of hydroponic technology packages and the emergence of interest and motivation to do the cultivation and production of vegetable crops hydroponically are growing. Cadres utilize limited land for farming by applying hydroponic technology according to standard operating procedures.